Analisis Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Organisasi - Meyla Faiya; Prawistyan Fajar Putra Utama (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This article aims to analyze the role of human resource management in improving organizational performance and formulate strategic recommendations based on improvements in human resource management practices. The theoretical foundations used include strategic human resource management theory, organizational performance theory, and work motivation theory, which are used to examine the functions of workforce planning, competency development, performance appraisal, and reward systems. This study employed a qualitative, descriptive-analytical approach, with data collection techniques including in-depth interviews, non-participant observation, and documentation studies. Data analysis was conducted using an interactive qualitative analysis model that encompasses data reduction, data presentation, and conclusion drawing. The analysis results indicate that workforce planning based on organizational needs, continuous competency development, an objective performance appraisal system, and a performance-based reward system are directly related to increased effectiveness, productivity, and stability of organizational performance. Furthermore, efforts to improve human resource management practices through policy evaluation, strengthening strategic planning, enhancing internal communication, and data-driven decision-making have proven to be a strong foundation for formulating strategic recommendations for the organization. The study's conclusions confirm that the systematic and strategic integration of human resource management functions is a key factor in achieving sustainable organizational performance and adapting to changes in the work environment.